Some approaches to the independence of Peru and the independence of Central America - Betancourt Rivera, José (2021)
The independence processes in Central America and Peru are the result of a set of thoughts and actions of change of the Spanish colonial system, conceived by various characters, who promoted emancipation and outlined the new structure of the liberal State in the first half of the 19th century, based on the principle of the separation of powers, a concept bequeathed by the French school. In both processes, two wise men who exerted a notable influence stand out, José Cecilio del Valle in Central America, and Hipólito Unanue in Peru, who with their reflection and dedication were decisive in the formation of consensus that forged the emancipation and creation of new independent political units.